Early Sensory Deprivation Leads to Differential Inhibitory Changes in the Striatum During Learning - Paraouty, Nihaad; Mowery, Todd M. (Frontiers in Neural Circuits, 2021)
The corticostriatal circuit has been identified as a vital pathway for associative learning. However, how learning is implemented when the sensory striatum is permanently impaired remains unclear. Using chemogenetic techniques to suppress layer 5 auditory cortex input to the auditory striatum, learning of a sound discrimination task was significantly impacted in freely moving Mongolian gerbils, in particular when this suppression occurs early on during learning. Whole-cell recordings sampled throughout learning revealed a transient reduction in postsynaptic (GABAA) inhibition in both striatal D1 and D2 cells in normal-hearing gerbils during task acquisition. In contrast, when the baseline striatal inhibitory strengths and firing rates were permanently reduced by a transient period of developmental sensory deprivation, learning was accompanied by augmented inhibition and increased firing rates. Direct manipulation of striatal inhibition in vivo and in vitro revealed a key role of the transient inhibitory changes in task acquisition. Together, these results reveal a flexible corticostriatal inhibitory synaptic plasticity mechanism that accompanies associative auditory learning.